Pendampingan Dan Pengembangan Dalam Menumbuhkan Kesadaran Akan Lingkungan Sehat Di Sekolah Sungai Gunung Anyar Melalui Program CSR PLN Peduli - Zahra Afifah Salsabilah Rasyid; G. Oka Warmana (Lembaga Pengembangan Kinerja Dosen, 2024)
Education is an effort to prepare students to improve the quality of human resources through mentoring and training methods for future roles. Awareness of the importance of protecting the environment has become a concern in society. In this case, assistance and development regarding the importance of protecting the environment is carried out for students at the Sungai Gunung Anyar School. This aims to form a generation that is aware, caring and responsible for the environment, as well as creating a sustainable society in the future.